Kebijakan Luar Negeri Feminis Swedia (2014-2018) - Maha, Irayomi F; Pattipeilohy, Shary Charlotte Henriette (Journal of International Relations, 2021)
In 2014, for the first time Sweden declared itself a country with a feminist foreign policy. The statement that drew international attention and attention was delivered by the Swedish foreign minister, Margot WallstrÓ§m, who is an activist for women and gender equality. In implementing this policy, there are six external policies carried out by Sweden which are implemented by the Swedish foreign ministry and the Swedish International Development Cooperation Agency (SIDA). The six policies include; fulfillment of human rights, freedom from acts of physical, mental and sexual violence, participation of women in preventing and resolving conflicts in the pre and post-conflict period, participation in elections, fulfillment of economic and development rights and finally the right to reproduce and sexually healthy. can analyze Sweden's reasons for implementing these six policies. The unit of analysis in foreign policy consisting of individuals, countries and the international system is used. This research is an explanative research type and qualitative research type with literature research data collection techniques and uses congruent methods to analyze data. The results of this study indicate that the three unit level analyzes, both individual, state and international system, encourage the formation of feminist foreign policy from Sweden